Oxidative stress in cystic fibrosis patients with Burkholderia cenocepacia airway colonization: relation of 8-isoprostane concentration in exhaled breath condensate to lung function decline - Fila, Libor; Grandcourtová, Alžběta; Chládek, Jaroslav; Musil, Jaromír (Folia microbiologica, 2014)
The association between oxidative stress and neutrophilic inflammation in cystic fibrosis (CF) lung disease is well recognized. 8-Isoprostane is a product of non-enzymatic oxidation of arachidonic acid. The aim of the present study was to examine the relationship between lung function decline and 8-isoprostane concentrations in exhaled breath condensate (EBC) in CF patients with Burkholderia cenocepacia airway colonization. Concentrations of 8-isoprostane in EBC were measured in 24 stable CF patients with B. cenocepacia airway colonization. The median (interquartile range) age of the cohort was 23.9 (22.0; 26.6) years. All patients underwent clinical examinations and pulmonary function tests at the time of EBC collection and in 1-, 3-, and 5-year intervals. 8-Isoprostane concentrations in EBC correlated to 1- and 3-year declines of forced expiratory volume in 1 s (FEV1) with r(S) values of -0.511 (p = 0.0011) and -0.495 (p = 0.016), respectively. In multiple regression analysis, 8-isoprostane concentrations in EBC were the only independent predictor for 1-year FEV1 decline (p = 0.01). When the median value of 8-isoprostane concentration in EBC (10.0 pg/mL) was used as a cutoff, subgroups of patients with lower and higher level of oxidative stress had significantly different median (interquartile range) FEV1 declines in 1-year interval, -2.4% (-5.3; 0.8) and -7.3% (-10.3; -5.8) predicted (p = 0.009). In conclusion, 8-isoprostane concentrations in EBC correlated to short-term lung function decline in CF patients with B. cenocepacia airway colonization. This correlation reflects the role of oxidative stress in CF lung pathogenesis and contributes to prediction of prognosis in these patients.
Keywords: respirační funkční testy; Male; vydechnutí; Opportunistic Infections; Time Factors; Forced Expiratory Volume; dinoprost; mužské pohlaví; Dinoprost; Burkholderia Infections; Burkholderia cenocepacia; Oxidative Stress; Adult; mladý dospělý; Cystic Fibrosis; oportunní infekce; Young Adult; ženské pohlaví; Humans; Respiratory Function Tests; časové faktory; usilovný výdechový objem; dospělí; oxidační stres; Female; Exhalation; lidé; cystická fibróza; infekce bakteriemi rodu Burkholderia